STUDY OF ENVIRONMENTALLY SOUND AND ENERGY-EFFICIENT METHODS OF CHEMICAL PRODUCTION IN THE CONTEXT OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Мустафаев Шухрат Элбекович (American Journals, 2026)
The article discusses modern approaches to the development of environmentally friendly and energy-efficient methods of chemical production. The key principles of sustainable development, the use of green technologies, new generation catalysts, renewable energy sources and closed production cycles are analyzed. efficiency.
Keywords: Sustainable development, green chemistry, energy efficiency, environmental safety, catalysis, chemical production.